Vibrações em sistemas bidimensionais - Peixoto, Renato de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Vibrations and oscillations are present in our daily lives, in microscopic structures to macroscopic. Motivated by these characteristics, is proposes to analyze through classical molecular dynamics simulations, with the aid of AIREBO potential, the effects of vibrations and traveling waves in two-dimensional structures at the nanoscale using graphene and its derivatives. Initially we intend to study the directions of longitudinal and transverse propagations through mechanical derangement and examining the occurrence of deformations and, if there are diffraction characteristics in optimum materials and materials with defects

Vibrações e oscilações estão presentes no nosso cotidiano, em estruturas microscópicas até macroscópicas. Motivado por essas características, este trabalho propõe a analisar por meio de simulações de dinâmica molecular clássica, com o auxílio do potencial AIREBO, os efeitos das vibrações e ondas progressivas, em estruturas bidimensionais, em escala nanométrica utilizando grafeno. Inicialmente pretendemos estudar os sentidos de propagação longitudinal e transversal através de perturbações mecânicas e examinar a ocorrência de deformações assim como, se há características de difração em materiais ideais e materiais com defeitos
Keywords: Vibração; Grafeno; Difração; Dinamica molecular